Equal Pay for Similar Work - Gentile Passaro, Diego; Kojima, Fuhito; Pakzad-Hurson, Bobak (American Economic Review, 2026)
Equal pay laws increasingly require that workers with different group identities doing “similar” work are paid equal wages within firm. We study such “equal pay for similar work” (EPSW) policies theoretically and test our models’ predictions empirically using evidence from a 2009 gender-based Chilean EPSW. Under EPSW, firms segregate their workforce by gender. When there are more men than women in a labor market, EPSW increases the gender wage gap. (JEL J16, J31, J38, K31, O15)